The Effect of Work from Home (WFH) Culture on Employee Performance for Consultants in Indonesia - Rivano, Muhammad Ilham; Dharmestha, Dhanez Wastu; Halim, Michael Lestario (Indonesian Business Review, 2025)
COVID-19 has changed the work culture among workers around the world due to its contagious nature. This study aims to address the effect of work-from-home culture on employee performance, specifically for consultants in Indonesia. This study was conducted using a quantitative method with data obtained from 334 respondents through online questionnaires. Furthermore, this study is using multiple regression analysis to know the impact of WFH Culture on Employee Motivation and Employee Satisfaction and the impact of Employee Motivation and Employee Satisfaction on Employee Performance. In this study we found that WFH does positively affect Employee Motivation and Satisfaction, thus increasing the Employee performance of consultants in Indonesia. We further strengthened this by using regression analysis. With this study, we hope to help consulting firms enforce the best workplace scenario to ensure the best possible employee performance. This research paper became the first study in Indonesia to discuss the impact of WFH Culture on Employee Performance with the Mediating Role of Employee Motivation and Employee Satisfaction for consultants in Indonesia.